Multiple modifiable maternal, household and health service factors are associated with maternal nutrition and early breastfeeding practices in Burkina Faso - Kim, Sunny S.; Ouédraogo, Césaire T.; Zagré, Rock Romaric; Ganaba, Rasmané; Zafimanjaka, Maurice G.; Tharaney, Manisha; Menon, Purnima (Wiley, 2023)
Low coverage of effective nutrition interventions in many high-burden countries, due to service provision and demand factors, result in poor uptake of recommended practices and nutrition outcomes. We examined the factors that influence maternal nutrition and early breastfeeding practices and determined the extent that the key factors could improve these practices in two regions in Burkina Faso. We used household survey data among pregnant (n = 920) and recently delivered women (n = 1840). Multivariable regression analyses were conducted to identify the determinants of a diverse diet and iron-folic acid (IFA) supplement consumption, weight monitoring during pregnancy and early initiation of breastfeeding (EIBF). Population attributable risk analysis was used to estimate how much the outcomes can be improved under optimal conditions of interventions that address the modifiable determinants. During pregnancy, 21% of women achieved minimum diet diversity (MDD-W), 70% consumed 90+ IFA tablets and 65% were weighed 4+ times; EIBF was 40%. Nutrition knowledge was associated with MDD-W (odds ratio [OR]: 3.2), 90+ IFA (OR: 1.5) and EIBF (OR: 1.9). Positive social norms and family support were associated with 90+ IFA (OR: 1.5). Early and 4+ ANC visits were associated with 90+ IFA (OR: 1.5 and 10) and 4+ weight monitoring (OR: 6.2). Nutrition counselling was associated with 90+ IFA (OR: 2.5) and EIBF (OR: 1.5). Under optimal programme conditions, 41% of women would achieve MDD-W, 93% would consume 90+ IFA, 93% would be weighed 4+ times and 57% would practice EIBF. Strengthening the delivery and uptake of interventions targeted at these modifiable factors has the potential to improve maternal nutrition practices.